Depolymerization of Poly (L-lactic acid) under Hydrothermal Conditions - FAISAL, MUHAMMAD; SAEKI, TAKASHI; TSUJI, HIDETO; DAIMON, HIROYUKI; FUJIE, KOICHI (Asian Journal of Chemistry, 2010)
Depolymerization of poly (L-lactic acid) was conducted under hydrothermal conditions at the temperature range of 160-350ºC and for a period of 3 h. The results show that the reaction temperature and time affect the extent of depolymerization and optical selectivity. The optimum conditions on depolymerization of poly (L-lactic acid) were attained at 270ºC and 8 min of reaction time. Higher optical purity of L-lactic acid was obtained with a yield of 96 %. A study on the effect of temperature on the optical purity of lactic acid product demonstrated that L-lactic acid was predominant at low range temperature of 250-270ºC. At higher temperature, optical purity was reduced and racemization occured. The experimental results showed that the method was found to be simple and promising for chemical recycling of poly (L-lactic acid) into its monomer.